2016
DOI: 10.1111/jocn.13188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of home care services on caregivers' burden and satisfaction

Abstract: Practical strategies for providing home care services should be developed through a concrete assessment of the family dynamics and the needs of family caregivers. Health professionals should play a pivotal role in performing the assessment and in developing interventions to strengthen supportive family functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…Resilience in caring for others was also observed among caregivers who had strong family relationships. The results indicate that the burden of and satisfaction with care are not necessarily associated with the offer of support services; however, care may lead to satisfaction, despite the overload, when there is the presence of another caregiver, in caregivers with higher education levels, and particularly in situations in which family life is satisfactory (Kim & Yeon, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience in caring for others was also observed among caregivers who had strong family relationships. The results indicate that the burden of and satisfaction with care are not necessarily associated with the offer of support services; however, care may lead to satisfaction, despite the overload, when there is the presence of another caregiver, in caregivers with higher education levels, and particularly in situations in which family life is satisfactory (Kim & Yeon, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study (Kim & Yeon, ) showed that the support of home care services was not significant to reduce overload and to bring satisfaction to caregivers. A functional family was the most significant factor for such satisfaction, since the home care service does not provide the necessary support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A sobrecarga física e emocional percebida pelos cuidadores familiares no desenvolvimento do CD pode ocasionar no adoecimento dos familiares cuidadores, em interrupções no seu estilo de vida e restrições nas atividades de lazer e trabalho do cuidador familiar, levando ao isolamento social. 24…”
Section: Discussionunclassified
“…O SAD deve avaliar a dinâmica familiar e as necessidades dos cuidadores e, os profissionais de saúde devem desempenhar um papel fundamental nas intervenções, com o propósito de fortalecer o funcionamento da família e oferecer apoio 38 . Outra possibilidade de intervenções foram: implementação de Home Care (HC), de forma organizada, que é uma modalidade de atenção fundamental para o cuidado de idosos e sua rede informal 39 .…”
Section: Estratégias De Enfrentamento No âMbito Social: Políticas Púbunclassified